2022
DOI: 10.3390/biology11010114
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Ligands Induce Antiviral Effects Targeting Perturbed Lipid Metabolism during SARS-CoV-2, HCV, and HCMV Infection

Abstract: The manipulation of host metabolisms by viral infections has been demonstrated by several studies, with a marked influence on the synthesis and utilization of glucose, nucleotides, fatty acids, and amino acids. The ability of virus to perturb the metabolic status of the infected organism is directly linked to the outcome of the viral infection. A great deal of research in recent years has been focusing on these metabolic aspects, pointing at modifications induced by virus, and suggesting novel strategies to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…Stimulation of PPARγ by natural or synthetic agonists may modulate the cytokine storm typical of viral infection by preventing cytokine overproduction and the inflammatory cascade ( 6 ) ( 27 ). Several natural PPARγ ligands have been proposed to treat COVID-19 ( 8 ). Due to its ability to reduce inflammatory parameters, the PPARγ agonist pioglitazone has also been proposed as an effective treatment for COVID-19 patients with diabetes, hypertension, and cardiovascular comorbidities ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of PPARγ by natural or synthetic agonists may modulate the cytokine storm typical of viral infection by preventing cytokine overproduction and the inflammatory cascade ( 6 ) ( 27 ). Several natural PPARγ ligands have been proposed to treat COVID-19 ( 8 ). Due to its ability to reduce inflammatory parameters, the PPARγ agonist pioglitazone has also been proposed as an effective treatment for COVID-19 patients with diabetes, hypertension, and cardiovascular comorbidities ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that respiratory virus, such as a respiratory syncytial virus (RSV), alter PPARγ expression ( 6 , 7 ). In addition, PPARγ ligands are proposed as anti-SARS-CoV-2 drugs based on their anti-inflammatory, antioxidant and immunomodulatory properties ( 8 , 9 ). Several PPARγ agonists have been documented to attenuate inflammation and alleviate influenza infection in mouse studies.…”
Section: Introductionmentioning
confidence: 99%
“…Observed increased CD36 gene expression in both survivors and non-survivors may be a consequence of PPARγ activation and here with remains increased after 7 days in the ICU. By targeting inflammation, ACE2 and the WNT/β-catenin pathway, PPARγ agonists were suggested to be interesting candi-dates for SARS-CoV-2 therapy due to modulation of the cytokine storm by pre-venting the cytokine overproduction [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FXR agonists can provoke the expression of PPARα, which possesses potent immunomodulatory effects in SARS-CoV-2 infection (Fantacuzzi et al 2022 ). PPARα agonists can lessen pulmonary inflammation, lipotoxicity, and metabolic derangement induced by SARS-CoV-2 infection (Fantacuzzi et al 2022 ).…”
Section: Fxr and Signaling Pathways In Covid-19mentioning
confidence: 99%
“…Furthermore, FXR agonists can provoke the expression of PPARα, which possesses potent immunomodulatory effects in SARS-CoV-2 infection (Fantacuzzi et al 2022 ). PPARα agonists can lessen pulmonary inflammation, lipotoxicity, and metabolic derangement induced by SARS-CoV-2 infection (Fantacuzzi et al 2022 ). Besides, in vitro study displayed that fenofibrate inhibits SARS-CoV-2-mediated cytopathic in Vero E6 cell lines at a concentration of 20 µM (Rodon et al 2021 ).…”
Section: Fxr and Signaling Pathways In Covid-19mentioning
confidence: 99%